2015
DOI: 10.1016/j.celrep.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-22 Gates Long-Term Heterosynaptic Plasticity in Aplysia through Presynaptic Regulation of CPEB and Downstream Targets

Abstract: The maintenance phase of memory-related long-term facilitation (LTF) of synapses between sensory and motor neurons of the gill-withdrawal reflex of Aplysia depends on a serotonin (5-HT)-triggered presynaptic upregulation of CPEB, a functional prion that regulates local protein synthesis at the synapse. The mechanisms whereby serotonin regulates CPEB levels in presynaptic sensory neurons are not known. Here, we describe a sensory neuron-specific microRNA 22 (miR-22) that has multiple binding sites on the mRNA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…For example, the propensity of CPEB to transition from a soluble to aggregated conformation is intrinsically dependent on protein expression level. As mentioned earlier, transcription of ApCPEB is upregulated in response to 5-HT, leading to elevated protein expression and subsequent aggregation by a variety of structural mechanisms (Raveendra et al 2013;Fiumara et al 2015). Moreover, CPEB expression is regulated by microRNAs (miRNAs).…”
Section: Aggregation Of Functional Prions Is Regulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the propensity of CPEB to transition from a soluble to aggregated conformation is intrinsically dependent on protein expression level. As mentioned earlier, transcription of ApCPEB is upregulated in response to 5-HT, leading to elevated protein expression and subsequent aggregation by a variety of structural mechanisms (Raveendra et al 2013;Fiumara et al 2015). Moreover, CPEB expression is regulated by microRNAs (miRNAs).…”
Section: Aggregation Of Functional Prions Is Regulatedmentioning
confidence: 99%
“…Moreover, CPEB expression is regulated by microRNAs (miRNAs). In particular, a neuron-specific miRNA, miRNA-22, inhibits ApCPEB mRNA through multiple 3 0 UTR binding sites and is downregulated by serotonin (Fiumara et al 2015). Inhibition of miR-22 simulates the effect of serotonin treatment, further increasing CPEB levels and enhancing long-term facilitation.…”
Section: Aggregation Of Functional Prions Is Regulatedmentioning
confidence: 99%
“…Several putative mechanisms for maintaining PKMζ have been proposed, including positive feedback loops at the levels of PKMζ mRNA transcription (Chen et al, 2014; Hernandez et al, 2014; Ko et al, 2016), translation of the PKMζ message (Fiumara et al, 2015; Jalil, Sacktor, & Shouval, 2015; Westmark et al, 2010), and PKMζ protein stability (Sacktor, 2011). How these mechanisms become engaged during memory formation and thus sustain PKMζ during memory maintenance are fundamental questions for elucidating how memories are stored.…”
Section: Discussionmentioning
confidence: 99%
“…This raised the ques- tion: How does the heterosynaptic modulator 5-HT-which induces learning-related longterm plasticity of sensorimotor neuron synapses-determine the initial up-regulation, and the consequent conversion of CPEB into its aggregated state in the presynaptic sensory neurons? In search of a mechanism whereby 5-HT up-regulates the levels of ApCPEB in sensory neurons, Fiumara et al (2015) identified an Aplysia microRNA 22 (miR-22) that is expressed in sensory neurons. MiR-22 is down-regulated by 5-HT and inhibition of miR-22 increases CPEB levels and enhances LTF, mimicking the effect of 5-HT-dependent up-regulation of CPEB.…”
Section: Microrna-22 Gates Long-term Heterosynaptic Plasticity In Aplmentioning
confidence: 99%